Disruption of ATRX-RNA interactions uncovers roles in ATRX localization and PRC2 function - Wenqing Ren; Nicole Medeiros; Robert Warneford-Thomson; Phillip Wulfridge; Qingqing Yan; Joyce Bian; Simone Sidoli; Benjamin A. Garcia; Emmanuel Skordalakes; Eric Joyce; Roberto Bonasio; Kavitha Sarma (Nature Communications, 2020)
ATRX is an RNA binding protein that mediates targeting of polycomb repressive complex 2 (PRC2) to genomic sites. Here the authors identify the RNA binding region and show that the RNA binding is required for ATRX localization and for its recruitment of PRC2 to a subset of polycomb targets.